2008
DOI: 10.1186/1471-2229-8-98
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterisation and comparative analysis of a starch synthase IV gene in wheat: functional and evolutionary implications

Abstract: BackgroundStarch is of great importance to humans as a food and biomaterial, and the amount and structure of starch made in plants is determined in part by starch synthase (SS) activity. Five SS isoforms, SSI, II, III, IV and Granule Bound SSI, have been identified, each with a unique catalytic role in starch synthesis. The basic mode of action of SSs is known; however our knowledge of several aspects of SS enzymology at the structural and mechanistic level is incomplete. To gain a better understanding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 71 publications
6
108
0
Order By: Relevance
“…The amino acid variations in the catalytic domain were predicted to be located in the α-helix and β-pleated sheet of A domain and irregular curls inside the crack. The above structure was consistent with the domains of TaSSIVb (Leterrier et al, 2008) and rice Wx protein and catalytic center prediction (Li et al, 2012). …”
Section: Structure Prediction Of Waxy Proteinsupporting
confidence: 68%
“…The amino acid variations in the catalytic domain were predicted to be located in the α-helix and β-pleated sheet of A domain and irregular curls inside the crack. The above structure was consistent with the domains of TaSSIVb (Leterrier et al, 2008) and rice Wx protein and catalytic center prediction (Li et al, 2012). …”
Section: Structure Prediction Of Waxy Proteinsupporting
confidence: 68%
“…It has been reported that two isoforms of SSIV exist in plants: SSIVa and SSIVb, which are expressed in the endosperm and leaves, respectively [39,112,158]. Recently, the role for the SSIV class has been primarily shown to be in starch granule initiation in Arabidopsis, although it may also be involved in producing short branches [145].…”
Section: Soluble Starch Synthasementioning
confidence: 99%
“…In recent years, cloning of starch enzyme genes has improved our understanding of starch synthesis (Jain et al, 2008b;Leterrier et al, 2008). Several cDNAs encoding SBEs have been isolated from rice, wheat, maize, and barley (Kim et al, 1998;Mutisya et al, 2003;Han et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, research aimed at regulating starch biosynthesis and improving starch quality is imperative. Developments in molecular biology have resulted in various starch biosynthesis management methods, ranging from genetic engineering to conventional breeding (Hirose and Terao, 2004;Song et al, 2004;Leterrier et al, 2008).…”
Section: Introductionmentioning
confidence: 99%